A New Heligmonellid Species (Nematoda) from Oligoryzomys nigripes (Rodentia: Sigmodontinae) in the Atlantic Forest, Brazil - Souza, Joyce G. R. (2009)
Stilestrongylus lanfrediae n. sp. is described from the small intestine of Oligoryzomys nigripes  (Cricetidae: Sigmodontinae) collected in the Atlantic Forest (Rio de Janeiro State, Teresópolis, Brazil). The new species shows some similarities with S. stilesi, S. freitasi, S. inexpectatus, S. moreli, and S. andalgala, but it can be distinguished from these species by the following combination of characters: 26 ridges in male and 25 in female at the mid-body, asymmetrical caudal bursa with a pattern of type 2-2-1, with rays 6 markedly shorter than other lateral rays, rays 8 inserted asymmetrically on dorsal trunk and shorter than it, and a proportion spicules length in relation body length (SpL/BL) of 25-29%. The new species is also distinguished from other species of Stilestrongylus by the asymmetry of the branches of the dorsal ray, and by having the longest spicules.